Dark triad and social media addiction: the mediating roles of coping strategies - Wong, Bernie Zi Ru; Goh, Sin Jie; Hui, Jie Yeng (2020)
The excessive use of social media will result in overall low well-being among undergraduates. DT is said to be a significant predictor of social media addiction. The limited guidance from experts in lowering social media addiction indirectly reflects the importance of adopting good coping strategies. Moreover, the correlations between the three variables are not clearly investigated in Malaysia. The current study aims to investigate how DT and coping strategies serve as a significant predictor for social media addiction among UTAR undergraduates in the multiculturalism context of Malaysia. A total 230 participants were recruited via purposive sampling in UTAR Kampar campus. Data was collected through paper-and-pen survey. However, only 219 participants have completed the survey and fulfilled the criteria of (i) studying as undergraduate at UTAR Kampar campus; (ii) have at least one social media account. Short DT scale (SD3), Brief Coping Orientation to Problems Experienced Inventory (COPE), and Bergen Social Networking Addiction Scale (BSNAS) were used to measure desirable variables. The correlation analysis indicated that Machiavellianism, psychopathy, emotion-focused coping strategy and avoidance-focused coping strategy positively predicted social media addiction. Besides, there is no significant relationship between narcissism and problem-focused coping strategies towards social media addiction. The results of the current study contributed to gaining awareness among the responsible parties, implementing constructive strategies and filling in the gaps in the pool of research on findings regarding DT, coping strategies and social media addiction among Malaysian undergraduates.